Increased Frequency of Complement C4 "Null" Alleles in Autoimmune Hepatitis - AL-Obeidy, Eman S.; Mousawy, Khalida M.; AL-Akayshi, Raghad J H; Kamil, Laith A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Human leukocyte antigen (HLA) is the most polymorphic genetic system in man. The genes of this region influence susceptibility to certain diseases.Patients and methods: Immunofixation test is the method used to asses C4 polymorphism of 100 blood samples of 60 AIH patients and 40 healthy normal controls.Results: An increased frequency of C4A*Q0 was observed for patients group versus control group with P-value (0.003).Conclusions: This finding demonstrated that C4A*Q0 might play a role in AIH susceptibility.